2020
DOI: 10.1021/acs.oprd.9b00438
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Access to a Great Diversity of Complex Biorelevant γ-Lactams Thanks to a Tunable Cascade Multicomponent Process

Abstract: This reviews surveys the preparation of a great diversity of complex biorelevant γ-lactam backbones thanks to scalable copper(I)-catalyzed cascade multicomponent processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It should be noted that substituted γ–hydroxy-γ-butyrolactams [ 26 ], which the 5 belongs to, act as a convenient source of corresponding N -acyliminium ions upon treatment with acids [ 27 ]. The latter undergoes the electrophilic substitution with electron-rich arenes, including indole derivatives [ 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that substituted γ–hydroxy-γ-butyrolactams [ 26 ], which the 5 belongs to, act as a convenient source of corresponding N -acyliminium ions upon treatment with acids [ 27 ]. The latter undergoes the electrophilic substitution with electron-rich arenes, including indole derivatives [ 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…[23,24] Besides the permeability in Caco-2 and MDCK cell system across the BBB, evaluation of the permeability across the skin/ epidermal linings is of great importance when it comes to the transversal drug delivery as well as the unintended exposure of harmful chemical entities. [25][26][27] In this regard, the skin permeability score (Log Kp) for the newly synthesized spirooxindole-oxofuran was reported to be negative (fromÀ 4.011 toÀ 3.887 cm/h for 4 d and 4 a, respectively), an acceptable range of Log Kp for therapeutic agents. [28] The fate of the drugs beyond absorption into the blood to the target tissues is governed by a set of factors (i. e., high M.W., solubility, and HBAs/HBDs) but plasma protein binding (PPB), perhaps, has been established amongst the major detrimental factors.…”
Section: Spirooxindole-oxofurans (4 A-d) Have Acceptable Adme Propertiesmentioning
confidence: 99%
“…Based on our previous reports, the hemiaminal group of 3hydroxyisoindolin-1-ones 1 may be generated through the nucleophilic addition reaction of primary amines into 3-alkylidenelactones. [21][22][23] However, several reports demonstrated that high reaction temperature and long reaction time were required for this transformation leading to the high cost of production and environmental issues. 13,24,25 To best of our knowledge, the scale-up of this reaction has not been reported.…”
Section: Introductionmentioning
confidence: 99%